Enhanced Toxicity for Mice of Combinations of Antibiotics with Escherichia coli Cells or Salmonella typhosa Endotoxin - Rose, W. C. (1971)
Enhanced lethality for BALB/c mice has been observed after the administration of Salmonella typhosa endotoxin with either actinomycin D, cycloheximide, or nogalamycin. The dose of actinomycin D required to kill half of the mice (LD(50)) was 0.8 mg/kg in normal animals, 0.35 mg/kg in mice administered 0.08 mg of endotoxin per kg, and 0.28 mg/kg in mice administered 0.2 mg of endotoxin per kg. The LD(50) of endotoxin in normal mice was 12 mg/kg and in mice given 0.4 mg of actinomycin D per kg was 0.067 mg/kg. The LD(50) of actinomycin D in mice administered 1.8 × 10(8) live Escherichia coli cells per kg or 1.8 × 10(9) heat-killed E. coli cells per kg was reduced to 0.4 mg/kg. The LD(50) of cycloheximide was 181 mg/kg in normal animals and 28 mg/kg in mice administered 4 mg of endotoxin per kg. The LD(50) of endotoxin in mice given 120 mg of cycloheximide per kg was 0.02 mg/kg. Enhanced lethality due to various combinations of cycloheximide and endotoxin was abolished by pretreatment of mice with endotoxin. The LD(50) of nogalamycin was 21 mg/kg in normal mice and 13 mg/kg in mice receiving 1 mg of endotoxin per kg.